SHAPING THE FUTURE OF ISLAMIC BANKING AND FINANCE: A LEGAL PERSPECTIVE - Kadi, Sanaa (International Journal of Islamic Banking and Finance Research, 2023)
After the inception of Islamic banking and finance (IBF) in the global financial industry, IBF became a new alternative form of ethical finance based on Islamic economic thought.  According to classical thought, the essence of Islamic economics is not to prohibit making a profit but to prioritize people’s well-being and, hence, enjoy the profit. This study examines the regulation and functioning of Islamic financial institutions (IsFIs), including their compliance with Sharia law. It explores the ethical considerations surrounding IsFIs by examining how their financial services align with the Sustainable Development Goals (SDGs). The study aims to shed light on the challenges and opportunities within the IBF sector, ultimately contributing to a deeper understanding of its role in promoting ethical finance and sustainable development. This study employs an empirical legal research approach to investigate the legal framework of IBF. The results reveal that by effectively highlighting ethical foundations and objectives, Islamic finance will attract a larger market of Muslims and arouse the interest of a wider audience of stakeholders who are not just interested in avoiding financial transactions that support prohibited practices. The findings of this study suggest that a major obstacle to the massive growth of the Islamic banking and finance sector is the existence of contradictions that depend especially on the excessively liberal accreditation of Islamic banks as “Sharia compliant.”JEL Classification Codes: E44 G10 G20.